Associação do polimorfismo genético do receptor 2A da serotonina (5-HT2A) com incontinência urinária em mulheres idosas - Noronha, Jorge Antônio Pastro (2008)
Introduction: Previous studies showed a possible association between the T102C polymorphism of the serotonin 2A receptor (5-HT2A) and urinary incontinence in the elderly. Since serotonin is involved in the modulation of bladder sphincter control, such association is biologically plausible. Since the pharmacological treatment of urinary incontinence (UI) includes the use of serotonin reuptake inhibitors, complementary studies of this polymorphism are of scientific and clinical importance. Objectives: The aims of this study in older women living in a senior living community were: (1) to describe and compare the allelic and genotypic frequencies of the 102C polymorphism of the serotonin 2A receptor (5-HT2A) in incontinent and continent individuals; (2) to describe and compare the urodynamic parameters in incontinents carrying different genotypes/alleles; (3) to describe and compare the frequency of the urodynamic types of urinary incontinence (stress, urge and mixed) in incontinent individuals carrying different genotypes/alleles; and (4) to describe and compare the impact of UI on the quality of life in incontinent individuals carrying different genotypes/alleles. Methodology: A case-control study was conducted including 68 incontinent older women (submitted to urodynamic evaluation) and 162 continent older women (self-reporting). The criteria for exclusion were: use of diuretics, diabetes, non-Caucasian individuals, and severe mobility and neurological disturbances. The polymorphism was analyzed by the PCR-RFLP technique. The Ethics Committee approved the study, and all participants signed an informed consent form. Results: Incontinent older women showed a significantly greater frequency of the TT genotype (TT= 34.8%, CC= 19.3%, TC= 45.9%) compared to continent older women (TT=17%, CC=23.3%, TC=59.7%) and the general sample of the population (TT=21.5%, CC=16.6%, TC=61.9%) (p=0.001). The genetic frequencies of the three samples were in Hardy-Weinberg equilibrium. Urodynamic analysis showed a significant association between the TT genotype and greater detrusor pressure at maximal cystometric capacity, lower maximal cystometric capacity and reduced bladder compliance. The TT genotype also showed a higher prevalence of urge UI (44%) than did the other genotypes (p=0.01). Analyses of indicators of quality of life and UI demonstrated a greater negative impact in carriers of the C allele (CC+TC). Conclusion: Together, the results suggest that the T102C polymorphism of the 5-HT2A receptor gene has a physiological effect on the lower urinary tract of humans. This hypothesis needs to be confirmed by complementary studies. The effect of an imbalance in the quantity of this receptor, which occurs in the TT genotype, could be associated with a greater chance or urge UI in older women.